AMERICAN PERSPECTIVES ON SUICIDALITY AMONG MEN IN POLAND - ROMANIUK, JAROSŁAW R.; KOTLARSKA-MICHALSKA, ANNA; FARKAS, KATHLEEN J. (Society Register, 2021)
This article examines sociological, psychological, and suicidological research on the determinants of male suicide to explore the fact that Polish men complete suicide 7.4 times more than women, a frequency twice as high as in the US. This paper is based upon an examination of relevant literature and statistical databases. A keyword search was completed in both Polish and English language databases. Ideals of masculinity and negative social attitudes towards a non-binary view of gender may increase stressors and discourage men in Poland from revealing their problems while seeking support, explaining the high rates of suicide completion among Polish men. Suicide prevention programs must tackle gender conceptualizations and alcohol use patterns as well as increase avenues for male help-seeking behaviors. These changes will require political and religious organizations to confront the weakening of male hegemony as the organizing principle for family and society. This paper explores the increased rate of male suicide in Poland from the perspective of gender.